Quantum dot induced acute changes in lung mechanics are mouse strain dependent. (24th August 2018) - Scoville, David K.; White, Collin C.; Botta, Dianne; An, Dowon; Afsharinejad, Zahra; Bammler, Theo K.; Gao, Xiaohu; Altemeier, William A.; Kavanagh, Terrance J.
Abstract: Introduction: Concerns have been raised regarding occupational exposure to engineered nanomaterials (ENMs). Potential impacts on lung function from inhalation exposures are of concern as the lung is a sensitive ENM target in animals. Epidemiological data suggest that occupational exposure to ENMs may impact respiratory and cardiovascular health. Quantum dots (QDs) are ENMs with outstanding semiconductor and fluorescent properties with uses in biomedicine and electronics. QDs are known to induce inflammation and cytotoxicity in rodents and high dose exposures impact lung function 2 weeks after exposure. However, effects of mouse strain and the temporality of QD effects on lung function at more occupationally relevant doses have not been well-established. Objective: We evaluated the impact of QD exposure on respiratory mechanics in C57BL/6J and A/J mice. Previous work found a greater initial inflammatory response to QD exposure in A/J mice compared to C57BL/6J mice. Thus, we hypothesized that A/J mice would be more sensitive to QD-induced effects on lung mechanics. Methods: C57BL/6J and A/J mice were exposed to 6 μg/kg Cd equivalents of amphiphilic polymer-coated Cd/Se core, ZnS shell QDs via oropharyngeal aspiration. Lung mechanics were measured using forced oscillation, and inflammation was characterized by neutrophils and cytokines in bronchoalveolar lavage fluid. Results: Both strains showed signs of QD-induced acute lung inflammation. However, lung mechanics were impacted by QD exposure in A/J mice only. Conclusions: Our findings suggest that susceptibility to QDs and similar ENM-induced changes in lung function may depend at least in part on genetic background.